Endoscopic Guided Dilations without Intralesional Corticosteroid Injections: Pediatric Crohn’s Patients Case Series - Leo Fawaz; Yousif Slim; Peter N. Freswick (Reports)
Background and Clinical Significance: The treatment for pediatric Crohn’s disease (CD) has shifted over the years from steroids and immunomodulators to biologics with the goal of histological and clinical remission. Endoscopic balloon dilation (EBD) has been utilized for stricturing disease, even in the pediatric population. EBD has been shown to be effective and minimally invasive, though historically, has been performed on patients with persistent mucosal inflammation. As such, intralesional corticosteroid (ILC) injections have been traditionally utilized during EBD. However, intralesional corticosteroid efficacy among pediatrics patients in deep endoscopic remission is unknown. Case Presentation: We report four patients that demonstrated at least initial successful dilations without intralesional steroid injections. Conclusions: The use of ILC injections during routine EBDs in pediatric patients should be further explored in randomized control trials.